There is Only One Mind/Body Problem - Harnad, Stevan (Theoria et Historia Scientiarum, 2008)
In our century a Frege/Brentano wedge has gradually been driven into the mind/body problem so deeply that it appears to have split it into two: The problem of “qualia” and the problem of “intentionality.” Both problems use similar intuition pumps: For qualia, we imagine a robot that is indistinguishable from us in every objective respect, but it lacks subjective experiences; it is mindless. For intentionality, we again imagine a robot that is indistinguishable from us in every objective respect but its “thoughts” lack “aboutness”; they are meaningless. I will try to show that there is a way to re-unify the mind/body problem by grounding the “language of thought” (symbols) in our perceptual categorization capacity. The model is bottom-up and hybrid symbolic/nonsymbolic.